The Social Model of Disability: a sociological tool for social emancipation - França, Tiago Henrique (Pontifícia Universidade Católica de São Paulo, 2013)
This article presents the as yet little known Social Model of Disability, as well as part of itstheoretical development. By understanding disability as a social construct, the model hassupported the struggle for the social integration of disabled people. In addition to defining it,the article discusses criticisms of the model and part of its theoretical development. The socialmechanisms that orient discrimination against people with deficiency are exposed, based on amaterialist analysis of the issue.